Dampak Pertumbuhan Ekonomi Terhadap Kualitas Lingkungan Hidup di Provinsi Pulau Sumatera - Akbar Maulana Ramadhan (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
Economic development is an effort to raise people's living standards. It is hoped that economic growth will result in a higher quality of community life. Economic growth and environmental quality are inextricably linked. On the one hand, economic growth can provide benefits such as higher living standards and increased consumption. On the other hand, economic growth places a burden on the environment in the form of utilization of natural resources, waste and pollution which threatens environmental sustainability. Therefore, this study aims to analyse the impact of economic growth on environmental quality. The case study in this research is in the province of Sumatra Island. This research uses panel data for 2016 to 2019 obtained from BPS and the Ministry of Environment and Forestry. The data is processed using the random effect model estimation with the log-linear regression model. The results showed that partially the variables of economic growth, employment, changes/reductions in the area of land cover, agriculture and mining did not have a significant effect on the environmental quality index in the Province of Sumatra Island for the 2016-2019 period. Meanwhile, industry variables have a significant effect on the environmental quality index in the province on Sumatra Island for the 2016-2019 period.